Pair-bonding and social experience modulate new neurons survival in adult male and female prairie voles (Microtus ochrogaster) - Analía E. Castro; Raymundo Domínguez-Ordoñez; Raymundo Domínguez-Ordoñez; Larry J. Young; Francisco J. Camacho; Daniela Ávila-González; Raúl G. Paredes; Raúl G. Paredes; Nestor F. Díaz; Wendy Portillo (Frontiers Media S.A., 2022)
Prairie voles are a socially monogamous species that, after cohabitation with mating, form enduring pair bonds. The plastic mechanisms involved in this social behavior are not well-understood. Neurogenesis in adult rodents is a plastic neural process induced in specific brain areas like the olfactory bulbs (OB) and dentate gyrus (DG) of the hippocampus. However, it is unknown how cell survival is modulated by social or sexual experience in prairie voles. This study aimed to evaluate if cohabitation with mating and/or social exposure to a vole of the opposite sex increased the survival of the new cells in the main and accessory OB and DG. To identify the new cells and evaluate their survival, voles were injected with the DNA synthesis marker 5-bromo-2'-deoxyuridine (BrdU) and were randomly distributed into one of the following groups: (A) Control (C), voles that did not receive any sexual stimulation and were placed alone during the behavioral test. (B) Social exposure (SE), voles were individually placed in a cage equally divided into two compartments by an acrylic screen with small holes. One male and one female were placed in opposite compartments. (C) Social cohabitation with mating (SCM), animals mated freely. Our findings demonstrated that SCM females had increases in the number of new cells (BrdU-positive cells) in the main olfactory bulb and new mature neurons (BrdU/NeuN-positive cells) in the glomerular layer (GlL). In contrast, these new cells decrease in males in the SE and SCM conditions. In the granular cell layer (GrL), SCM females had more new cells and neurons than the SE group. In the accessory olfactory bulb, in the anterior GlL, SCM decreased the number of new cells and neurons in females. On the other hand, in the DG, SCM and SE increase the number of new cells in the suprapyramidal blade in female voles. Males from SCM express more new cells and neurons in the infrapyramidal blade compared with SE group. Comparison between male and females showed that new cells/neurons survival was sex dependent. These results suggest that social interaction and sexual behavior modulate cell survival and influence the neuronal fate in a sex-dependent manner, in the OB and DG. This study will contribute to understand neural mechanisms of complex social and pair bond behaviors in the prairie voles; supporting adult neurogenesis as a plastic mechanism potentially involved in social monogamous strategy.